Twenty‐year results of the randomized European Organization for Research and Treatment of Cancer trial 22922/10925 evaluating internal mammary chain and medial supraclavicular lymph node irradiation in stage I–III breast cancer - Orit Kaidar‐Person; Caroline G. Weltens; Catherine Fortpied; Luc J. E. E. Scheijmans; Carine Y. Kirkove; Volker Budach; Karine Peignaux‐Casasnovas; Mariacarla Valli; Max Peters; Femke van der Leij; Sofia Rivera; Nicola Weidner; et al. (CA: A Cancer Journal for Clinicians, 2026)
Abstract European Organization for Research and Treatment of Cancer trial EORTC 22922/10925 evaluated internal mammary and medial supraclavicular (IM‐MS) lymph node irradiation (IM‐MS‐RT) in patients with stage I–III breast cancer. Eligible patients had involved axillary nodes and/or centrally/medially located tumors regardless of nodal involvement. The primary end point was overall survival, secondary end points were disease‐free survival, distant metastases‐free survival, breast cancer mortality, and any breast recurrence. Between 1996 and 2004, 4004 patients were randomized. The median patient age was 54 years. At a median follow‐up of 22.2 years, 1550 (38.7%) patients died, of whom 796 (51.4%) died from breast cancer. At 20 years, the overall survival rate was 61.8% in the control group versus 61.0% in the IM‐MS‐RT group (hazard ratio [HR], 1.00; p = .967); the disease‐free survival rate was 49.0% versus 48.2%, respectively (HR, 0.97; p = .515); and the distant metastases‐free survival rate was 59.8% versus 58.9%, respectively (HR, 0.97; p = .578). The breast cancer mortality rate was 22.4% in the control group and 18.6% in the IM‐MS‐RT group (HR, 0.82; p = .006), whereas the rate of deaths not from breast cancer or from unknown causes was 15.8% versus 20.4%, respectively (HR, 1.26; p = .002). Lung fibrosis, cardiac fibrosis, and cardiac diseases were more frequent after IM‐MS‐RT versus no IM‐MS‐RT (6.3% vs. 3.2%, 2.7% vs. 1.7%. and 15.2% vs. 11.7%, respectively); and the rates of severe cardiac and lung morbidities (scores of 3 or 4) were 1.9% versus 1.7% and 0.3% versus 0.0%, respectively. Breast cancer mortality at 20 years was statistically significantly lower after IM‐MS‐RT, but deaths not from breast cancer increased after 15 years, resulting in no long‐term benefit of IM‐MS‐RT on overall survival. Therefore, the authors strongly call for very long‐term follow‐up of treatments for prognostically favorable cancers such as breast cancer.